2015
DOI: 10.1002/ptr.5374
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Osteoclast Differentiation by Ginsenoside Rg3 in RAW264.7 Cells via RANKL, JNK and p38 MAPK Pathways Through a Modulation of Cathepsin K: An In Silico and In Vitro Study

Abstract: Various studies have demonstrated that overexpression of cathepsin K (Cat-K) causes excessive bone loss, which ultimately leads to a variety of bone diseases including osteoporosis. Therefore, inhibition of Cat-K signifies a potential therapeutic target in osteoporosis treatment. Ginsenoside Rg3 is one of the most promising compound of Panax ginseng Meyer (P. ginseng) with numerous biological activities. Thus, in recent study the inhibitory effect of Rg3 isolated from P. ginseng was investigated in order to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…The particular cell morphology changes indicated that mesenchymal cells differentiated into epithelial cells (osteoblasts/cementoblasts in the present study); thus, CTSK affected the differentiation of PDLSCs. Previous studies on the role of CTSK in cell differentiation have mainly focused on osteoclast differentiation (Siddiqi et al ., ). In addition, CTSK regulates adipogenic (Han et al ., ) and osteogenic differentiation (Morko et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The particular cell morphology changes indicated that mesenchymal cells differentiated into epithelial cells (osteoblasts/cementoblasts in the present study); thus, CTSK affected the differentiation of PDLSCs. Previous studies on the role of CTSK in cell differentiation have mainly focused on osteoclast differentiation (Siddiqi et al ., ). In addition, CTSK regulates adipogenic (Han et al ., ) and osteogenic differentiation (Morko et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…RAD23B, MAPK8 and TLK2 have been shown to be involved in DNA damage response [18]. Effect of ginsenosides on MAPK has been well documented [19][20][21]. A Chinese herbal medicine containing ginsenosides was found to attenuate H 2 O 2 -induced injury in PC12 cells by inhibiting Akt and MAPK signaling pathways [22].…”
Section: Discussionmentioning
confidence: 99%
“…Over expression of cathepsin K causes excessive bone loss (Siddiqi et al, 2015; Zhuoet al, 2014). In this study, we found that Br-H A reduced the RANKL-induced expression of cathepsin K. TRAP is an iron-binding protein that is highly expressed in osteoclasts and also induced in differentiation of osteoclasts (Reddy et al, 1995).…”
Section: Discussionmentioning
confidence: 99%